Aplikasi Pengolahan Data Spbu ( Stasiun Pengisian Bahan Bakar Umum ) Pt. Sinar Mustika Bintan Km 19 Bintan Timur - ELVIANNA; Nurul Saepul; Doni Kristianto (Jurnal Bangkit Indonesia, 2019)
This thesis report is prepared based on the results of the analysis of the ongoing data collection system as well as the results of designing a new system at PT. SINAR MUSTIKA BINTAN SPBU Km 19 East Bintan. The results of the analysis show that manual data processing causes several problems so that the system performance becomes less efficient. To fix the deficiencies that exist in the system that is being implemented, a new system is designed to increase work efficiency. The data processing application developed can help solve problems that have existed before. This application was built using Borland Delphi 7.0. With this new system and application, it is hoped that the work process will be more efficient and can be improved.